2020
DOI: 10.3390/su12083471
|View full text |Cite
|
Sign up to set email alerts
|

Model Proposal for Diagnosis and Integration of Industry 4.0 Concepts in Production Engineering Courses

Abstract: In Industry 4.0, people need to be able to handle the vast amount of information from machines. In this sense, for Industry 4.0, higher education institutions play a fundamental role. The methodology of this article sought to identify the knowledge required by Industry 4.0 in the literature; carry out a diagnosis of the courses currently offered by Brazilian universities and the need to incorporate new knowledge, and validate the model in a real application. The survey is classified as exploratory, bibliograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…I4.0 represents the integration of a production system through digitalization and automation of manufacturing mechanisms and processes (RAMPASSO et al, 2019;CEZARINO et al, 2019;PIO et al, 2021;QUELHAS & SOUZA, 2020;MUMMOLO et al, 2019), and the use of technologies that seek to improve the economic performance of a company (QUELHAS et al, 2020;DURÃO et al, 2017). SILTORI et al ( 2021) characterize six principles: interoperability, virtualization, decentralization, real-time capacity, service orientation, and modularity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…I4.0 represents the integration of a production system through digitalization and automation of manufacturing mechanisms and processes (RAMPASSO et al, 2019;CEZARINO et al, 2019;PIO et al, 2021;QUELHAS & SOUZA, 2020;MUMMOLO et al, 2019), and the use of technologies that seek to improve the economic performance of a company (QUELHAS et al, 2020;DURÃO et al, 2017). SILTORI et al ( 2021) characterize six principles: interoperability, virtualization, decentralization, real-time capacity, service orientation, and modularity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The articles indicate that the objective of this research is in line with research opportunities related to the skills of new engineers required by Industry 4.0 (QUELHAS & SOUZA, 2020 and OLIVEIRA & SANTOS, 2020), such as "people management, service orientation, negotiations, and cognitive flexibility" (RAMPASSO et al, 2019). There is a need for discussions on organizational guidelines (BORGES and TAN, 2017;CEZARINO et al, 2019;SILTORI et al 2021;HU, 2021;NICOLETA-CLAUDIA et al, 2021;PIRES et al, 2021;OLIVEIRA, MACHADO & PEREIRA, 2021;QUELHAS et al, 2020;MUMMOLO et al, 2019). DURÃO et al (2017) deepen the study of a specific organizational structure "central factory and distributed site".…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…With sensors incorporated in almost all industrial components and equipment, ubiquitous cyber-physical systems, and analysis of all important data, Engineering 4.0 education [24] should focus on skills that lead to digitalization in the manufacturing sector [25]. New, multifunctional professions are required as a result of Industry 4.0.…”
Section: Urge For Education Of Industry 40 Technologiesmentioning
confidence: 99%
“…Literature [13] explores the different influences on the development and implementation of Industry 4.0 in universities for sustainable education, and the study emphasizes the importance of practical expertise and digital technologies to be fostered during studies in higher education. Literature [14] conducted a survey and research to determine the requirements that Industry 4.0 places on graduates and found that current HEIs are not preparing graduates sufficiently for the role of Industry 4.0 engineers, pointing out that the key knowledge required relates to Big Data, Advanced Simulation, and Virtual Reality technologies. Literature [15] examines the role played by universities in smart city projects (SCP) based on quantitative and qualitative data collected from the bottom-up and finds that universities have a role as integrators, delivering relevant research and application-oriented talents.…”
Section: Introductionmentioning
confidence: 99%